Supercritical CO2 Extraction of Carotenoids (Astaxanthin, Adonirubin, and Adonixanthin) from Paracoccus carotinifaciens: Improved Z‐Isomer Ratio and Recovery of Carotenoids via High‐Temperature Extraction. Issue 7 (26th May 2022) - Honda, Masaki; Murakami, Kazuya; Osawa, Yukiko; Kawashima, Yuki; Wasai, Masafumi; Hirasawa, Kazuaki; Kuroda, Ikuo
Abstract: The effects of high‐temperature supercritical CO2 (SC‐CO2 ) extraction on Z ‐isomerization and recovery of carotenoids (astaxanthin, adonirubin, and adonixanthin) from Paracoccus carotinifaciens are investigated. The high‐temperature extraction, especially at >100 °C,  not only increases the total Z ‐isomer ratio of carotenoids in the resulting extracts but also improves carotenoid recovery. For example, when the SC‐CO2 extraction is performed at 60 °C and 30 MPa with an entrainer (ethanol), the total Z ‐isomer ratio and the recovery of astaxanthin are 11.1% and 28.4%, respectively, whereas at 120 °C, the values increase to 54.2 and 56.4%, respectively. The significant improvement in the extraction efficiency of carotenoids at high temperatures can be attributed to the increase in the ratio of carotenoid Z ‐isomers with high solubility in SC‐CO2 . Moreover, the effects of extraction pressure and entrainer content on Z ‐isomerization and recovery of carotenoids are also investigated. The results show that higher pressure and ethanol content resulted in lower Z ‐isomer ratios and higher recoveries of carotenoids. As the Z ‐isomers of carotenoids have greater bioavailability and potentially exhibit superior biological activities than the all‐ E ‐isomers, high value‐added carotenoids, and higher yield can be simultaneously achieved with high‐temperature extraction. Practical applications : As carotenoid extraction is usually performed using toxic organic solvents, residual solvents are a serious concern. In addition, naturally occurring carotenoids (mainly the all‐ E ‐isomers) have low bioavailability. These are important issues that need to be overcome for the industrial use of carotenoids. The Z ‐isomer‐rich carotenoids obtained by SC‐CO2 extraction under high‐temperature conditions have great potential to solve these issues simultaneously. Abstract : This study investigates the effect of high‐temperature conditions on the extraction of carotenoids (astaxanthin, adonirubin, and adonixanthin) from Paracoccus carotinifaciens using supercritical CO2 . The high‐temperature extraction, especially at >100 °C, not only increases the total Z ‐isomer ratio of carotenoids in the resulting extracts but also improves carotenoid recovery.